Conceptual design of supersonic aircraft to investigate environmental impact - Villena Munoz, Cristina; Lawson, Craig P.; Riaz, Atif; Jaron, Robert (American Institute of Aeronautics and Astronautics (AIAA), 2024)
The SENECA ((LTO) noiSe and EmissioNs of supErsoniC Aircraft) project, funded under the EU Horizon 2020 framework, is dedicated to the exploration of future designs for supersonic business jets and supersonic commercial airliners, placing significant emphasis on minimising landing and take-off noise and mitigating emissions. The research outcomes are intended to inform discussions at ICAO level, providing scientific support to enhance the European perspective on regulatory requirements for novel supersonic aircraft. The overall aim of the research is the development of four different supersonic transport aircraft platforms, comprising both airframes and engines design. These aircraft configurations range from supersonic business jets, designed for cruise Mach numbers of 1.4 and 1.6, to large airliners capable of accommodating 100 passengers, with cruise Mach numbers of 1.8 and 2.2. In pursuit of the next generation of environmentally sustainable supersonic civil aircraft, the research employs a multi-disciplinary design optimisation strategy. This strategy primarily focuses on meeting the current noise regulations for subsonic aircraft during landing and take-off and secondly on reducing emissions levels. This paper details the conceptual development of the platforms specifications for the four supersonic aircraft designed within SENECA project. These specifications include geometrical and configuration data, performance characteristics, as well as mission trajectories and profiles.